Analysis of the factors influencing the adoption of digital extension services: evidence from the RiceAdvice application in Nigeria - Amoussohoui, R.; Arouna, A.; Bavorova, M.; Verner, V.; Yergo, Wilfried; Banout, J. (Informa UK Limited, 2024)
Purpose: The study evaluates new approach of digital extension services for the long-term adoption of digital extension technologies. We propose an indirect adoption approach to address following research questions. What socioeconomic factors influence rice farmers' decision to prefer one business profile over another? Which business profile is most preferred and likely to be adopted by rice farmers? What are the attributes and socioeconomic characteristics required to create the best business profile?Design/Methodology/Approach: Ten business profiles were tested with a sample size of 1440 farmers. Using the RiceAdvice as case study, we used choice experiment and the alternative-specific mixed logit model to determine most preferred business profile and analyze its determinants.Findings: The preferred business profile was predicted by gender, age, education level, rice production experience, technology knowledge, contact with extension agents, rice farm size, and household income. 49.4% of farmers selected cash payment after harvest at 9.70 USD/hectare for more than two seasons-contract as first adoption approach. Cash payment after harvest at 14.50 USD/hectare for one season-contract was chosen by 44.7% of farmers as the second option.Practical implications: Results highlight the ideal business profile, which considers all levels of education, with 14.50 USD/hectare/season as optimum price for cash payment after harvest and no access to credit.Theoretical implications: The study expands the applicability of new adoption approach combined with econometric approach in the context of digital extension service adoption.Originality/Value: This study revealed an indirect approach to the long-term adoption of digital extension technologies as most suitable for small holder farmers' adoption.